Intestinal Schistosomiasis among Primary Schoolchildren in Two On-Shore Communities in Rorya District, Northwestern Tanzania: Prevalence, Intensity of Infection and Associated Risk Factors. (16th October 2016) - Munisi, David Z.; Buza, Joram; Mpolya, Emmanuel A.; Kinung'hi, Safari M.
Abstract : In Tanzania, Schistosoma mansoni is of great public health importance. Understanding the prevalence and infection intensity is important for targeted, evidence-based control strategies. This study aimed at studying the prevalence, intensity, and risk factors of S. mansoni among schoolchildren in the study area. A cross-sectional study was conducted in Busanga and Kibuyi villages. Sampled 513 schoolchildren provided stool specimens which were examined using kato-katz method. Pretested questionnaire was used to collect sociodemographic data and associated risk factors. The prevalence of S. mansoni infection was 84.01%, with geometric mean egg intensity of 167.13 (95% CI: 147.19–189.79) eggs per gram of stool (epg). Other parasites detected were Ascaris lumbricoides (1.4%) and hookworms (1.4%). The geometric mean infection intensity in Busanga and Kibuyi were 203.70 (95% CI: 169.67–244.56) and 135.98 (95% CI: 114.33–161.73) epg, respectively. Light, moderate, and heavy infection intensities were 34.11%, 39.91%, and 25.99%, respectively. Village of residence, parent's level of education, toilet use, and treatment history were predictors of infection. The high prevalence and infection intensity in this study were associated with village, parent's level of education, inconsistent toilet use, and treatment history. To control the disease among at-risk groups, these factors need to be considered in designing integrated schistosomiasis control interventions.